Synthesis and elaboration of modified comb type (maleic anhydride-α-tetradecene) copolymers for cold flow improvers of biodiesel - Mai Thi Tuyet Phan; Boi Van Luu; Lan Ngoc pham (Vietnam Journal of Science, Technology and Engineering, 2021)
The maleic anhydride-α-tetradecene copolymer (OMAC) with an approximate relative maleic anhydride to α-tetradecene composition ratio of 1:1.2 was synthesized by free radical copolymerization. The copolymers were modified by the esterification reaction between the anhydride groups and the OH- group of hexadecanol. Comb-type (-maleic acid cetyl ester-co-α-tetradecene-) copolymers (MCEC) with various ratios of alkyl group/carboxyl group (r) were investigated. Upon cooling, the MCEC changed the crystallization state of the wax crystals, and reduced the pour point of the biodiesel, which was observed by pour point and dynamic viscosity testing. The MCEC efficiency that improved the cold flow properties of the biodiesel was found to be correlated to r. MCEC with r=2.76 was found to be the most effective in improving the flow ability of the palm oil biodiesel. Our study demonstrates the ability of MCEC3 at 1000 ppm concentration to reduce the pour point of palm oil biodiesel to 10.5oC and the dynamic viscosity up to 1.04 mPa.s. A correlation was found between the number and the length of the pendant alkyl groups of additives and the compositions of the fatty acid methyl ester of the biodiesel.